Exploring the mechanism underlying the cardioprotective effect of shexiang baoxin pill on acute myocardial infarction rats by comprehensive metabolomics. (15th September 2020) - Wu, Gaosong; Chen, Linlin; Gu, Yu; Hong, Ying; Ma, Junli; Zheng, Ningning; Zhong, Jing; Liu, Ai-Jun; Sheng, Lili; Zhang, Weidong; Li, Houkai
Abstract: Ethnopharmacological relevance: Shexiang Baoxin Pill (SBP) is a commercial Chinese medicine included in the Chinese Pharmacopoeia with well-established cardiovascular protect effect in clinic. However, the mechanism of SBP underlying protective effect on cardiovascular disease has not been clearly elucidated yet. Aim of the study: We aimed to investigate the underlying protective mechanisms of SBP on an acute myocardial infarction (AMI) rat model by using comprehensive metabolomics. Materials and methods: The rat model of AMI was generated by ligating the left anterior descending coronary artery. After two weeks of treatment with SBP, comprehensive metabolomics and echocardiography index was performed for a therapeutic evaluation. The wiff data were processed using Progenesis QI and metabolites were identified based on the database of HMDB and LIPIDMAPS. Meanwhile, the untargeted metabolomics data from LC-MS combined with correlation analysis to characterize the metabolic alterations. Results: The metabolomics profiles of different groups in different biological samples (heart, serum, urine and feces) were significantly different, in which a total of 217 metabolites were identified. AMI caused comprehensive metabolic changes in amino acid metabolism, glycerophospholipid metabolism and pyrimidine metabolism, while SBP reversed more than half of the differential metabolic changes, mainly affecting amino acid metabolism, butanoate metabolism and glycerophospholipid metabolism. Correlation analysis found that SBP could significantly alter the metabolic activity of six key metabolites (5-hydroxyindoleacetic acid, glycerophosphocholine, PS (20:4/0:0), xanthosine, adenosine and L-phenylalanine) related to AMI. The key role of these metabolites was further validated with correlation analysis with echocardiography indexes. Conclusion: This study demonstrated that SBP was effective for protecting cardiac dysfunction by regulating amino acid, lipid and energy metabolisms. The results also suggested that the modulation on gut microbiota might be involved the cardioprotective effect of SBP. Graphical abstract: Image 1